PENGARUH PENDIDIKAN, KOMPETENSI DAN DISIPLIN KERJA TERHADAP KINERJA PERANGKAT DESA DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING DI DESA KARANG SENGON, DESA KLABANG, DESA BLIMBING KECAMATAN KLABANG KABUPATEN BONDOWOSO - Dewi, Amelia Yasinta; Arief, Mohammad Yahya; Sari, Rini Kartika (Fakultas Ekonomi dan Bisnis, 2025)
Qualified human resources (HR) possess the knowledge, abilities, skills, and attitudes necessary for effective job performance. Organizations must take strategic steps to develop and enhance the quality of their human resources. One such strategy is through training programs that enable employees to acquire new knowledge and values, thereby enhancing their abilities and professionalism in performing their duties. Village governments still face various challenges in fulfilling their primary roles. These include a low level of education among village apparatus, the inability of some village officials to perform their duties—leading them to delegate responsibilities to others—and low levels of work discipline, which have become a public concern. Many village officials regularly arrive late to the office, thus hindering public service delivery. This study aims to examine the influence of education, competence, and work discipline on performance, with job satisfaction as an intervening variable in Karang Sengon Village, Klabang Village, and Blimbing Village, Klabang Sub-district, Bondowoso Regency. The sample was determined using a complete sampling technique, comprising 34 village apparatus members (excluding leadership). Data analysis and hypothesis testing were conducted using Structural Equation Modeling with Partial Least Squares (PLS-SEM). The hypothesis test results using SmartPLS 3.0 indicate that education has a positive but not significant effect on job satisfaction; competence has a positive and significant effect on job satisfaction; work discipline has a positive but not significant effect on job satisfaction; education, competence, and work discipline each have a positive but not significant effect on performance; job satisfaction also has a positive but not significant effect on performance. Furthermore, education, competence, and work discipline each have a positive but not significant effect on performance through job satisfaction.